Answer:
3 pounds
Step-by-step explanation:
a pound is 16oz so 3x16=48
b 3(6 +3x)
c 6 ( 3 + x)
d (3 + 2x)
Answer:
c:) 6(3 + 2x)
Step-by-step explanation:
The given expression is 18 + 12x. To simplify this expression, we can first look for any common factors that can be factored out. In this case, we can factor out 6, which gives:
18 + 12x = 6(3 + 2x)
So, the simplified expression 18 + 12x is 6(3 + 2x).
Answer: q = 13
because p and q are inverse
=> 26/10 = q/5
⇔ q = 26/10.5
⇔ q = 13
Step-by-step explanation: